The Fairchild books dictionary of interior design - Hinchman, Mark (Fairchild Books, 2014)
"With over 700 illustrations visually aligned with concise definitions of alphabetized entries, Dictionary of Interior Design, 3rd Edition, consolidates historic and modern terminology that all interior designers should know for both the residential and commercial sides of industry. New and revised definitions focus on key areas including technology, business practices, green design, universal design, and the global marketplace as well as historic furniture, stylistic features and periods. Appendices include an expanded appendix of designers and architects listing more women and international figures from the twentieth and twenty-first centuries, an updated appendix of professional organizations and associations, tables, and a new appendix of graphic standards. Fully updated by a practicing interior designer and architect with extensive industry knowledge, this expansive dictionary is an essential reference for students and design professionals." -- Publisher's website.